Situation Analysis of Malaria in Surat: A Hospital Based Study - Patel, Jitendra M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Recent challenges in dealing with prevention of malaria are urbanization and migration, construction activity, insecticide resistance, inadequate health and sanitation infrastructure, poor community participation and public private partnership. Surat city experienced the worst phase of malaria between 1987 to 1992. Methods: Cross-sectional study was carried out from December 2006 to March 2007 in malaria clinic in New Civil Hospital, Surat. On an average daily 8-10 patients for whom blood was collected were asked to come again after one week to collect the report of malaria. Study was included 500 participants in which 287 male and 213 female. Results: Most of male participants were student (24.4%), labor (23.7%) and factory worker (20.2) and most of female participants were house wife (50.7%), student (21.1%) and labor (7.5%). Almost 50.5% male participants got information regarding Malaria from poster, handball, hoarding and 50.2% female participants from TV, cinema slide, radio. Conclusions: Changing staff, including resident doctors and other staff needs to be oriented with the national guidelines regarding control of malaria and especially anti-malarial prescription. Malaria clinic can be an important place to educate the people regarding malaria control. Educating patients can go a long way for malaria control in urban area.